Hubungan Dukungan Petugas Kesehatan Terhadap Perilaku Individu dalam Pemanfaatan Layanan BPJS - Irma Finurina Mustikawati; Endang Sutisna Sulaeman; Achmad Arman Subijanto; Suminah Suminah (Jurnal Health Sains, 2023)
Economic development's primary goal is to make the community prosperous. EBSCO, ScienceDirect, and Proquest databases are used for both international and domestic literature searches. In the initial rounds of looking for journal articles, we discovered 25 papers between 20 and 22 using the keywords "health services," "BPJS," and "health professionals." Only roughly 10 of them are thought to be important. Only eight products, two of low quality, and five of medium quality satisfied all requirements. Increased health behavior among BPJS members is a result of the interaction between the structure and function of social agents in administering the health service system. Participants in BPJS Kesehatan in Wonogiri shown notable cooperation with hospitals and Puskesmas.